PENDEKATAN BELAJAR MELALUI KARYA POSTER DALAM MENGENALKAN MATERI GLOBALISASI PADA MATA PELAJARAN PKN UNTUK SISWA KELAS IV SD 1 NGEMBALREJO KABUPATEN KUDUS - Setiawan, Deka (Universitas Muria Kudus, 2016)
Research Approach Learning Through Work Poster In Introduce Content GlobalizationOn Civics Lesson For Students Grade IV SD 1 Ngembalrejo Interest problem in this researchthere are three that are the focus does skills of teachers in managing learning civics with posterwork approach in the introduction of globalization for students SD 1 Ngembalrejo Kudus,Knowing students' activity in learning civics with the approach of the work of the posters in theintroduction of globalization for elementary students SD 1 Ngembalrejo Kudus, Exposing thelearning outcomes of students in learning civics approach works poster in the introduction ofglobalization for elementary students 1 Ngembalrejo.Results of action research showed an increase learning outcomes Civics approaches tolearning through the work of the poster to introduce the material globalization. Improvedlearning outcomes is proved by research data cycle I and cycle II. This is evidenced by theincrease in the average value of pre cycle class until the second cycle. The value in the pre-cycleevaluation results using data from test scores were pure. Based on these data, the known valueof the average student with classical completeness 60.45 40.91%, there were 13 students whohave not completed and 9 students who pass. Teachers' teaching skills in managing the class oncivics learning approaches to learning through the work of the poster to introduce the materialin the first cycle of globalization gained 80.17% in the percentage of both criteria, on thesecond cycle increased to 84.91% with good criterion. Activities of students in participatingCivics Education materials globalization approaches to learning through the work of the posterto introduce the material in the first cycle of globalization gained 75.28% at both criteria,increased in the second cycle into 84.66% are in the very good Civics criteria approachlearning through the work of the poster to introduce the material globalization can improvelearning outcomes in the cognitive, affective and psychomotor. The increase in the cognitiveaspects seen in the first cycle to the second cycle is the average value of 69.55 rose to 77.05, theaspect of affective seen from the first cycle to the second cycle of 62.5% ie sufficient criteriarose to 84.43%, with good criterion, while the aspect of psychomotor seen the first cycle to thesecond cycle of 56.02% is sufficient criteria increased to 84.21% at both criteria.